2018
DOI: 10.3892/ol.2018.8374
|View full text |Cite|
|
Sign up to set email alerts
|

microRNA‑23a promotes cell growth and metastasis in gastric cancer via targeting SPRY2‑mediated ERK signaling

Abstract: microRNAs (miRs) serve important roles in various human cancer types. Recently, miR-23a has been indicated as an oncogene in gastric cancer, but the underlying mechanism remains unclear. In the present study, reverse transcription-quantitative polymerase chain reaction and western blot analysis was used to explore the effects of miR-23a in gastric cancer. Additionally, cell proliferation, migration and invasion were examined using an MTT assay, wound healing assay and Transwell assay, respectively. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Similarly, a previous study has revealed that miR-23a was highly expressed in gastric cancer tissues and cell lines. 19 According to the examination, highly expressed miR-23a in cancers of the digestive system was associated with a poor prognosis. 20 Another study demonstrated that OC tissues had a high miR-23a expression, which was consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a previous study has revealed that miR-23a was highly expressed in gastric cancer tissues and cell lines. 19 According to the examination, highly expressed miR-23a in cancers of the digestive system was associated with a poor prognosis. 20 Another study demonstrated that OC tissues had a high miR-23a expression, which was consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, low expression of Sprouty2 is associated with poor prognosis via the upregulation of FGFR2‐induced ERK activation, positive lymphatic invasion, and metastasis . MicroRNA‐23a, which is considered as an oncogene, is upregulated in gastric cancer samples and promotes cell proliferation and metastasis by targeting Sprouty2 . MicroRNA‐592 also enhances the proliferation and invasion of gastric cancer cells by targeting Sprouty2 .…”
Section: Roles Of Sprouty/spred During Tumorigenesis and Metastasismentioning
confidence: 99%
“…40 MicroRNA-23a, which is considered as an oncogene, is upregulated in gastric cancer samples and promotes cell proliferation and metastasis by targeting Sprouty2. 67 MicroRNA-592 also enhances the proliferation and invasion of gastric cancer cells by targeting Sprouty2. 41 In esophageal squamous cell carcinoma, lncRNA CCAT1 is upregulated and induces the histone methylation of the promoter of Sprouty4, resulting in the suppression of Sprouty4 expression.…”
Section: Sprouty/spred and Upper Digestive Tract Cancermentioning
confidence: 99%
“…miR-23a was downregulated in endometrial cancer, which inhibited the development of endometrial cancer by targeting SIX1 [17]. In contrast, in gastric cancer, miR-23a was upregulated with the promoting role in gastric cancer through targeting SPRY2 [18]. For breast cancer, a variety of miRNAs have been reported to play roles in its development, which provide novel therapeutic targets for the treatment of breast cancer, such as miR-449b-5p, miR-141, miR-200c, which were overexpressed in breast cancer tissues and cell lines [19,20], and miR-216a, miR-223, miR-132-3p, which were downregulated [21][22][23].…”
Section: Discussionmentioning
confidence: 98%